Scarlett's Sisters : Young Women in the Old South - Jabour, Anya (Book collections on Project MUSE., 2007)
'Scarlett's Sisters' explores the meaning of nineteenth-century southern womanhood from the vantage point of the celebrated fictional character's flesh-and-blood counterparts: young, elite, white women. Anya Jabour demonstrates that southern girls and young women faced a major turning point when the Civil War forced them to assume new roles and responsibilities as independent women. Examining the lives of more than 300 girls and women between the ages of fifteen and twenty-five, Jabour traces the socialization of southern white ladies from early adolescence to young adulthood.